Replicative DNA polymerases promote active displacement of SSB proteins during lagging strand synthesis - Cerrón, Fernando (Nucleic Acids Res, 2019)
Genome replication induces the generation of large stretches of single-stranded DNA (ssDNA) intermediates that are rapidly protected by single-stranded DNA-binding (SSB) proteins. To date, the mechanism by which tightly bound SSBs are removed from ssDNA by the lagging strand DNA polymerase without compromising the advance of the replication fork remains unresolved. Here, we aimed to address this question by measuring, with optical tweezers, the real-time replication kinetics of the human mitochondrial and bacteriophage T7 DNA polymerases on free-ssDNA, in comparison with ssDNA covered with homologous and non-homologous SSBs under mechanical tension. We find important differences between the force dependencies of the instantaneous replication rates of each polymerase on different substrates. Modeling of the data supports a mechanism in which strong, specific polymerase-SSB interactions, up to ∼12 k(B)T, are required for the polymerase to dislodge SSB from the template without compromising its instantaneous replication rate, even under stress conditions that may affect SSB–DNA organization and/or polymerase–SSB communication. Upon interaction, the elimination of template secondary structure by SSB binding facilitates the maximum replication rate of the lagging strand polymerase. In contrast, in the absence of polymerase–SSB interactions, SSB poses an effective barrier for the advance of the polymerase, slowing down DNA synthesis.